2023
DOI: 10.1039/d3py00809f
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic oligo(2-ethyl-2-oxazoline)s via straightforward synthesis and their self-assembly behaviour

James Lefley,
Zivani Varanaraja,
Ben Drain
et al.

Abstract: The synthesis of poly(2-oxazoline)s offers an unparalleled degree of functionalization when fabricating smart, functional polymers for biomedical uses. The termination of 2-oxazoline polymerisations by direct endcapping can be exploited to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Moreover, further end-group analysis of P1 and P2 by MALDI-TOF spectrometry revealed greater functionalization compared to NMR; a recent study found a similar observation where MALDI analysis disclosed the presence of only the end-capped product, indicating higher functionalization efficiency compared to NMR analysis . The MALDI analyses of P1 and P2 , shown via Figure and Figure S3, both displayed a primary distribution that matched closely with the calculated molecular weight, with an average repeating unit of 99.1, which is identical to the molecular weight of the EtOx monomer repeating unit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, further end-group analysis of P1 and P2 by MALDI-TOF spectrometry revealed greater functionalization compared to NMR; a recent study found a similar observation where MALDI analysis disclosed the presence of only the end-capped product, indicating higher functionalization efficiency compared to NMR analysis . The MALDI analyses of P1 and P2 , shown via Figure and Figure S3, both displayed a primary distribution that matched closely with the calculated molecular weight, with an average repeating unit of 99.1, which is identical to the molecular weight of the EtOx monomer repeating unit.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, this methodology has been exploited for a range of studies and applications. 45,46 Herein, we utilize these accessible techniques to synthesize a library of POxs with varying degrees of polymerization and anthracene functionalization; this is conveyed via Scheme 1. Direct end-capping of 9-anthracenecarboxylic acid onto poly(2ethyl-2-oxaozline) (PEtOx) and poly(2-isostearic-2-oxazoline) (PiStOx) is demonstrated for the first time to the best of our knowledge.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation